The contribution of water radiolysis to marine sedimentary life - Justine F. Sauvage (Nature Portfolio, 2021)
The extent to which chemical products of water radiolysis could sustain subseafloor microbial life is unknown. Here the authors show that sediment catalyzes radiolytic production of H2 and oxidants, providing the primary energy source for life in ancient marine sediment.